Life Cycle Assessment (LCA) of Environmental and Energy Systems - Luca Ciacci; Fabrizio Passarini (Energies, 2020)
The transition towards renewable energy sources and “green” technologies for energy generation and storage is expected to mitigate the climate emergency in the coming years [...]